Sweden : Adjoining the Guarantee Pension with NDC - Nelson, Kenneth; Nieuwenhuis, Rense; Alm, Susanne (World Bank, Washington, DC, 2019)
This paper analyzes old-age incomes in Sweden from a pension policy perspective, focusing on both the economic position of elderly citizens and the redistributive effects of the pension system’s different parts. The empirical analyses show that each subsequent cohort that reaches retirement age faces higher relative poverty risks than previous cohorts. The relative decline in the value of the guaranteed minimum pension vis-à-vis the real income growth of wage earners brings to the forefront the issues of indexation of the guarantee and the ceiling on the means-tested housing benefits like the basic safety net for pensioners.